Visual field defects after radiosurgery versus temporal lobectomy for mesial temporal lobe epilepsy: Findings of the ROSE trial. (December 2018) - Quigg, Mark; Barbaro, Nicholas M.; Ward, Mariann M.; Chang, Edward F.; Broshek, Donna K.; Langfitt, John T.; Yan, Guofen; Laxer, Kenneth D.; Cole, Andrew J.; Sneed, Penny K.; Hess, Christopher P.; Yu, Wei; et al.
Highlights: Patients with lesional mesial temporal epilepsy were randomized by surgical technique. VF defects were compared after temporal lobe SRS versus open epilepsy surgery. VFD incidence and severity did not differ significantly by treatment arm. VFD severity was not associated with seizure remission or driving status. VFD occurs in about 90% of patients regardless of surgical method. Abstract: Purpose: Stereotactic radiosurgery (SRS) may be an alternative to anterior temporal lobectomy (ATL) for mesial temporal lobe epilepsy (MTLE). Visual field defects (VFD) occur in 9–100% of patients following open surgery for MTLE. Postoperative VFD after minimally invasive versus open surgery may differ. Methods: This prospective trial randomized patients with unilateral hippocampal sclerosis and concordant video-EEG findings to SRS versus ATL. Humphries perimetry was obtained at 24 m after surgery. VFD ratios (VFDR = proportion of missing homonymous hemifield with 0 = no VFD, 0.5 = complete superior quadrantanopsia) quantified VFD. Regressions of VFDR were evaluated against treatment arm and covariates. MRI evaluated effects of volume changes on VFDR. The relationships of VFDR with seizure remission and driving status 3 years after surgery were evaluated. Results: No patients reported visual changes or had abnormal bedside examinations, but 49 of 54 (91%) of patients experienced VFD on formal perimetry. Neither incidence nor severity of VFDR differed significantly by treatment arm. VFDR severity was not associated with seizure remission or driving status. Conclusion: The nature of VFD was consistent with lesions of the optic radiations. Effective surgery (defined by seizure remission) of the mesial temporal lobe results in about a 90% incidence of typical VFD regardless of method.